Lesion-Specific Peri-Coronary Fat Attenuation Index Is Associated With Functional Myocardial Ischemia Defined by Abnormal Fractional Flow Reserve - Ma, Shaowei; Chen, Xujiao; Ma, Yue; Liu, Hui; Zhang, Jiayin; Xu, Lei; Wang, Yining; Liu, Ting; Wang, Kunhua; Yang, Jinzhu; Hou, Yang (Frontiers in Cardiovascular Medicine, 2021)
Background The association between lesion-specific peri-coronary adipose tissue (PCAT) fat attenuation index (FAI) and abnormal invasive fractional flow reserve (FFR) is unclear. Method Data of patients who underwent coronary CTA and subsequent invasive coronary angiography (ICA) and FFR measurement within one week were retrospectively included. Lesion-specific FAI (FAIlesion), lesion-free FAI (FAInormal), epicardial adipose tissue (EAT) volume and attenuation were collected, as well as stenosis severity and plaque characteristics. Lesions with FFR < 0.8 were considered functionally significant. The association between FFR and each parameter was analyzed by logistic regression or receiver operating characteristic curve. Result A total of 227 patients from seven centers were included. EAT volume or attenuation, traditional risk factors and FAInormal (with vs without ischemia: -82 ±11 HU vs. -81 ± 11 HU，p=0.65) were not significantly different in patients with or without abnormal FFR. In contrast, lesions causing functional ischemia presented more severe stenosis, greater plaque volume and higher FAIlesion (with vs without ischemia: -71±8 HU vs. -76±9 HU, p<0.01). Additionally, the CTA-assessed stenosis severity (OR 1.06, 95%CI 1.04-1.08, p<0.01) and FAIlesion (OR 1.08, 95%CI 1.04-1.12, p<0.01) were determined to be independent factors that could predict ischemia. The combination model of these two CTA parameters exhibited a diagnostic value similar to ICA-assessed stenosis severity (AUC: 0.820 vs. 0.839, p=0.39). Conclusion It was FAIlesion, not general EAT parameters, that was independently associated with abnormal FFR and the diagnostic performance of CTA-assessed stenosis severity for functional ischemia was significantly improved in combination with FAIlesion.